Tajdid Ushul Fiqh’s Husein Muhammad And Reformulation Of Women’s Jurisprudence - Rohmah, Siti; Hamidah, Tutik; Zuhriah, Erfaniah; SJ, Fadil (Arena Hukum, 2024)
This study proposes ideas for reforming Husein Muhammad’s ushul fiqh to address and deconstruct the gender biases present in some aspects of Islamic law in Indonesia. Using a conceptual research approach through a literature study, this research finds that Husein Muhammad employed the method of reforming ushul fiqh when examining women’s fiqh issues. Husein Muhammad’s approach to tajdid in ushul fiqh includes Tawhid as the fundamental basis for understanding the Qur’an and hadith, interpreting the concept of asbâb al-nuzûl by examining the broader historical context of human traditions at the time of the Qur’an’s revelation, rather than a narrow focus, differentiating between muhkamat verses with universal values and mutasyabihat verses with particular dimensions, considering Makiyyah verses to have a universal dimension, in contrast to Madaniyyah verses which are seen as having specific dimensions, and typologizing verses into those with legal dimensions and those with informative dimensions, as well as distinguishing between legal hadiths and informative hadiths. The renewal of the epistemology of Islamic law proposed by Husein Muhammad aims to produce Islamic legal interpretations that are just and gender-equal, freeing women from the constraints of patriarchal culture and misogynistic fiqh texts.